3D visualization of discrete event simulation and its applications in virtual manufacturing - Zhong, Yongmin; Yuan, X. (Korea Institute of Science Technology, 2004)
This paper presents a new approach to create 3D visualisation from discrete simulation results. This approach connects discrete event simulation directly to 3D animation with its novel methods that analyze and convert discrete simulation results into animation events to trigger 3D animation. In addition, it constructs a 3D animation framework for the visualization of discrete simulation results. This framework supports the reuse of both the existing 3D animation objects and behaviour components, and allows the rapid development of new 3D animation objects by users with no special knowledge in computer graphics. This approach has been implemented with the software component technology. As an application in virtual manufacturing, visualizations of an electronic assembly factory are also provided in the paper to demonstrate the performance of this new approach.